2010
DOI: 10.1523/jneurosci.0063-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Persuasion-Induced Behavior Change from the Brain

Abstract: Although persuasive messages often alter people's self-reported attitudes and intentions to perform behaviors, these self-reports do not necessarily predict behavior change. We demonstrate that neural responses to persuasive messages can predict variability in behavior change in the subsequent week. Specifically, an a priori region of interest (ROI) in medial prefrontal cortex (MPFC) was reliably associated with behavior change (r ϭ 0.49, p Ͻ 0.05). Additionally, an iterative cross-validation approach using ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
294
3
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(324 citation statements)
references
References 23 publications
24
294
3
3
Order By: Relevance
“…The current study provides the first experimental evidence (to our knowledge) that changing activity within VMPFC alters subsequent trajectories of health behavior change. In past work, neural activity in VMPFC during exposure to messages designed to increase sunscreen use (45) and decrease smoking (46,59) has predicted messageconsistent behavior change up to 1 mo after message exposure, but these results have been correlational. The experimental manipulation of neural activity in VMPFC via a self-affirmation manipulation adds substantially to prior findings.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The current study provides the first experimental evidence (to our knowledge) that changing activity within VMPFC alters subsequent trajectories of health behavior change. In past work, neural activity in VMPFC during exposure to messages designed to increase sunscreen use (45) and decrease smoking (46,59) has predicted messageconsistent behavior change up to 1 mo after message exposure, but these results have been correlational. The experimental manipulation of neural activity in VMPFC via a self-affirmation manipulation adds substantially to prior findings.…”
Section: Discussionmentioning
confidence: 92%
“…Neural responses can be recorded as affirmation and subsequent persuasion occur, without requiring self-report assessments that could interfere with the message recipient's natural thought processes. In support of this idea, our team has used neural predictors to augment understanding of health behavior change in response to interventions in other domains (42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Self-affirmationmentioning
confidence: 99%
See 1 more Smart Citation
“…VMPFC is known to integrate multiple types of value signals [23] from limbic and prefrontal regions [35], which may serve as a summary value signal in response to social influence. Indeed, individual differences in VMPFC activity during persuasive message exposure successfully predicted participants' changes in sunscreen use one week after the scanning session compared to baseline usage beyond the participants' self-reported attitudes toward sunscreen and intentions to change their behavior [36]. In addition, research examining the effectiveness of smoking quit messages found that increased activity in the VMPFC during ad exposure predicted reductions in smoking one month following the scanning session compared to baseline beyond a number of self-report measures collected [37].…”
Section: Predicting Behavior Changementioning
confidence: 92%
“…With this in mind, neural variables (e.g., structure, function, connectivity) can be hypothesized in advance and treated as predictor variables of relevant population level outcomes (103). This use of neuroimaging methods may contribute explanatory power that is not readily available from other sources and may be a source of convergent validity for identifying the best measures of behavior (103)(104)(105). Moreover, increasingly, there has been a shift from the assumption that the brain is only a dependent or independent variable but also can be a moderator and mediator of paths from experience to behavior or between genes, brain, and behavior (56,61,102,103,106).…”
Section: )mentioning
confidence: 99%